Effects of immersive virtual reality on limb motor function, balance, gait and quality of life after stroke: A systematic review and meta-analysis - Dana Islam; Ingela Marklund; Mia von Euler; Maria Jaensson (PLoS ONE, 2026)
Immersive virtual reality (IVR) has been increasingly integrated into stroke rehabilitation albeit the effectiveness across different outcome domains remains unclear. This study aimed to review evidence from randomized controlled trials evaluating the effects of IVR, used alone or in combination with conventional rehabilitation, on motor-, functional-, and participation-related outcomes after stroke. Ovid MEDLINE, Embase, Cochrane Library and CINAHL were screened up to April 2025 to identify eligible randomized controlled trials (RCTs). A systematic literature search was conducted. Randomized controlled trials including adults with stroke and evaluating immersive virtual reality interventions were eligible. Studies using non-immersive VR, non-randomized designs, or not reporting motor, functional, or participation outcomes were excluded. Meta-analyses were performed where data were sufficiently homogeneous; otherwise, outcomes were summarized descriptively. Risk of bias was assessed using standardized appraisal tools, and certainty of evidence was evaluated using the GRADE approach. Out of 3,574, we included 34 RCTs involving post-acute, subacute and chronic stroke survivors, with a total of1200 participants. Meta-analyses showed IVR, most commonly delivered in combination with conventional rehabilitation, to be associated with improvements in upper extremity motor impairment, particularly measured by the Fugl-Meyer Assessment Upper Extremity (FMA-UE). Small but significant effects were also found for selected gait parameters. In contrast, effects on functional performance, balance, and quality of life were inconsistent and could not be robustly quantified. The overall certainty of evidence ranged from low to very low, primarily due to heterogeneity, methodological limitations, and small sample sizes. In conclusion, IVR appears to be a promising and safe supplement to conventional stroke rehabilitation, particularly for improving motor impairment. However, evidence remains limited and inconsistent across functional outcomes. More well-designed, adequately powered trials with standardized interventions and clinically meaningful outcome measures are needed to clarify the role of IVR in stroke rehabilitation. PROSPERO (Registration number: CRD420250639792).